Suivi par teledetection des cultures de decrue dans la vallee du fleuve Senegal en saison froide 2000/2001. In FrenchEstimating crop yield in flood recession agriculture in the Senegal River Valley using remote sensing - Mane, L.K.; Fraval, P. (Societe Nationale d'Amenagement et d'Exploitation des Terres du Delta du fleuve Senegal et des vallees du fleuve Senegal et de la Faleme (SAED), 2001)
In the Senegal river floodplain, irrigated agriculture and traditional flood recession crops (mainly sorghum) coexist. The latter depends upon the extent of the annual flood, which is partly a function of the amount of water released from the upstream Manantali reservoir. Even though recession sorghum yield is clearly smaller than that of irrigated rice, this production system, because it covers a large area, is a major contributor to total food production in Podor and Matam departments. It is therefore important to quantify areas and yields. In collaboration with the West Africa Rice Development Association (WARDA) and the International Water Management Institute (IWMI), SAED has carried out a survey of the 2000-2001 agricultural campaign based on remote sensing and GIS analysis. In 2000, inundations in the Podor department covered 37.635 hectares. 3.277 million m3 of water were released from the Manantali reservoir specifically to support the natural flooding due to uncontrolled tributaries of the Senegal river. However, over the entire rainy season, the inflow into the reservoir exceeded the water released from it. In the Podor department, 18.998 hectares were cultivated, corresponding to 51% of the inundated area. In total, in both departments, the total area under sorghum cultivation amounted to 25.745 hectares in 2000-2001, that is only 44% of the area of the previous season, particularly wet. The total production of recession sorghum grain in the Matam department is about 4.075 tons and the average yield 638 kg/hectare. The method used gives reliable results, particularly a good relationship between yield and spectral response. It requires not more than 3 weeks of fieldwork but timing is crucial. Coupled with SAED?s Geographic Information System (GIS) and complementary to the survey of rice production using remote sensing analysis, this work provides a more accurate estimation of food production at the level of each Rural Community. It also provides objective information to assess the mutual influence of recession sorghum and irrigated rice cropping systems.